Protein expression changes induced in a malignant melanoma cell line by the curcumin analogue compound D6. Issue 1 (December 2016) - Pisano, Marina; Palomba, Antonio; Tanca, Alessandro; Pagnozzi, Daniela; Uzzau, Sergio; Addis, Maria; Dettori, Maria; Fabbri, Davide; Palmieri, Giuseppe; Rozzo, Carla
Abstract Background We have previously demonstrated that the hydroxylated biphenyl compound D6 (3E, 3′E)-4, 4′-(5, 5′, 6, 6′-tetramethoxy-[1, 1′-biphenyl]-3, 3′-diyl)bis(but-3-en-2-one), a structural analogue of curcumin, exerts a strong antitumor activity on melanoma cells both in vitro and in vivo. Although the mechanism of action of D6 is yet to be clarified, this compound is thought to inhibit cancer cell growth by arresting the cell cycle in G2/M phase, and to induce apoptosis through the mitochondrial intrinsic pathway. To investigate the changes in protein expression induced by exposure of melanoma cells to D6, a differential proteomic study was carried out on D6-treated and untreated primary melanoma LB24Dagi cells. Methods Proteins were fractionated by SDS-PAGE and subjected to in gel digestion. The peptide mixtures were analyzed by liquid chromatography coupled with tandem mass spectrometry. Proteins were identified and quantified using database search and spectral counting. Proteomic data were finally uploaded into the Ingenuity Pathway Analysis software to find significantly modulated networks and pathways. Results Analysis of the differentially expressed protein profiles revealed the activation of a strong cellular stress response, with overexpression of several HSPs and stimulation of ubiquitin-proteasome pathways. These were accompanied by a decrease of protein synthesis, evidenced by downregulation of proteins involved in mRNA processing and translation. These findings are consistent with our previous results on gene expression profiling in melanoma cells treated with D6. Conclusions Our findings confirm that the curcumin analogue D6 triggers a strong stress response in melanoma cells, turning down majority of cell functions and finally driving cells to apoptosis.